Konceptuel imperialisme og engageret sympati i forskning om kvindelige sexsælgere - Jeanett Bjønness (The Royal Danish Library, 2017)
Conceptual imperialism and engaged sympathy in research on female sex-sellers: This paper investigates academic knowledge production on sex-sellers’ everyday life and strategies. Methodological discussions are first contextualized in public discourse on prostitution in Denmark characterized by a highly polarized debate often opposing ‘the victim’ to ‘the autonomous individual’ and second in the researcher’s autobiography. The paper discusses how the researcher’s own classed and gendered experiences affect the ethnographic research process. Does attempted identification with informants sometimes obscure valuable knowledge? Does it even sometimes lead to unintended kinds of ‘othering’ or ‘epistemological imperialism’? The paper builds on data from long term fieldwork in a drop-in center for marginalized Danish women, life history interviews, and a critical reading of contemporary debates on prostitution in Denmark.